Is There a Role for Risk-Reducing Bilateral Breast Surgery in BRCA1/2 Ovarian Cancer Survivors? An Observational Study - Oliveira, Daniela (2023)
Risk-reducing surgeries are an option for cancer risk management in BRCA1/2 individuals. However, while adnexectomy is commonly recommended in breast cancer (BC) survivors, risk-reducing bilateral breast surgery (RRBBS) is controversial in ovarian cancer (OC) survivors due to relapse rates and mortality. Methods: We conducted a retrospective analysis of BRCA1/2- OC survivors, with OC as first cancer diagnosis. Results: Median age at OC diagnosis for the 69 BRCA1/2-OC survivors was 54 years. Median overall survival was 8 years, being significantly higher for BRCA2 patients than for BRCA1 patients (p = 0.011). Nine patients (13.2%) developed BC at a median age of 61 years. The mean overall BC-free survival was 15.5 years (median not reached). Eight patients (11.8%) underwent bilateral mastectomy (5 simultaneous with BC treatment; 3 RRBBS) at a median age of 56.5 years. The median time from OC to bilateral mastectomy/RRBBS was 5.5 years. Conclusions: This study adds evidence regarding a lower BC risk after BRCA1/2-OC and higher survival for BRCA2-OC patients. A comprehensive analysis of the competing risks of OC mortality and recurrence against the risk of BC should be individually addressed. Surgical BC risk management may be considered for longer BRCA1/2-OC disease-free survivors. Ultimately, these decisions should always be tailored to patients’ characteristics and preferences.